The plausibility of mind uploading - Žalec, Bojan (Poligrafi, 2025)
This article discusses the plausibility of uploading the human mind onto a non-biological digital medium. The concept of mind uploading has gained significant momentum due to advances in digital technology and artificial intelligence. This question is highly relevant for theology and religion because it addresses key theo-logical issues. Undoubtedly, mind uploading conflicts with religious and theologi-cal perspectives that view the human being as an inseparable unity of mind and body. Consequently, it should be examined from a theological standpoint. The author explores philosophical questions related to mind uploading, which are also very important for theology. He presents and critically examines the fundamental assumptions of mind uploading—namely dualism and functionalism—along with many arguments questioning its plausibility—including based on the biological limitations of consciousness, the phenomenological aspect of embodiment, the active perspective of consciousness, the significance of the body model in iden-tity, and the role of body in social integration, relationships, and daily life. He devotes a lot of space to explaining the importance of the (lived) body. He shows how difficult it is to see how a non-biological digital substrate could replace it. He concludes that the plausibility of mind uploading remains highly questionable, both scientifically and philosophically. Based on current evidence, it is reasonable to argue that the human mind is fundamentally dependent on its biological and bodily aspects and cannot be reproduced on non-biological digital substrates.
Keywords: biological aspects of the human mind; biološki vidiki človeškega uma; dualism; dualizem; fenomenologija telesa in uma; filozofija uma; funcitonalism; funkcionalizem; mind uploading; naložitev uma; phenomenology of the body and mind; philosophy of the mind